The impact of impaired tissue fixation in resected non-small-cell lung cancer on protein deterioration and DNA degradation. (April 2023) - Butter, Rogier; Halfwerk, Hans; Radonic, Teodora; Lissenberg-Witte, Birgit; Thunnissen, Erik
Highlights: Immunohistochemical staining intensity is higher in adequately fixated tumor areas. Immunohistochemical staining intensity is different within tumors, suggesting heterogeneous immunoreactivity. Independent of tumor fixation, DNA fragments rarely exceeded a length of 300 base pairs. The pathologist should be aware of the quality of tumor fixation during the interpretation of immunohistochemistry. Abstract: Objectives: The objective is to assess the impact of the quality of tissue fixation in surgical pathology on immunohistochemical (IHC) staining and DNA degradation. Materials and methods: Twenty-five non-small cell lung cancer (NSCLC) resection specimens were analyzed. After resection, all tumors were processed according to the protocols in our center. In haematoxylin and eosin (H&E) stained tissue slides, adequately- and inadequately fixed tumor areas were microscopically demarcated, based on basement membrane detachment. In 10 IHC stains ALK (clone 5A4), PD-L (clone 22C3), CAM5.2, CK7, c-Met, KER-MNF116, NapsinA, p40, ROS1, TTF1) the immunoreactivity in H-scores was determined in adequately- and inadequately fixed, and necrotic tumor areas. From the same areas DNA was isolated, and DNA fragmentation in base pairs (bp) was measured. Results: H-scores were significantly higher in H&E adequately fixed tumor areas in IHC stains KER-MNF116 (H-score 256 vs 15, p =0.001) and p40 (H-score 293 vs 248, p =0.028). All other stains showed a trend towards higher immunoreactivity in H&E adequately fixed areas. Independent of H&E adequatelty- or inadequately fixed areas, all IHC stains showed significant different IHC staining intensity within tumors, suggesting heterogeneous immunoreactivity (H-scores: PD-L1 123 vs 6, p  = 0.001; CAM5.2 242 vs 101, p =<0.001; CK7 242 vs 128, p =<0.001; c-MET 99 vs 20, p =<0.001; KER-MNF116 281 vs 120, p =<0.001; Napsin A 268 vs 130, p  = 0.005; p40 292 vs 166, p  = 0.008; TTF1 199 vs 63, p =<0.001). DNA fragments rarely exceeded a length of 300 bp, independent of adequate fixation. However, DNA fragments of 300 and 400 bp had higher concentrations in tumors with short fixation delay (<6 h vs >16 h) and short fixation time (<24 h vs >24 h). Conclusions: Impaired tissue fixation of resected lung tumors results in decreased IHC staining intensity in some parts of the tumor. This may impact the reliability of IHC analysis.